2020
DOI: 10.1016/j.molstruc.2020.128476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and electron distribution of 4-nitropyridine N-oxide: Experimental and theoretical study of substituent effects

Abstract: The molecular structure of 4-nitropyridine N-oxide, 4-NO 2 -PyO, has been determined by gas-phase electron diffraction monitored by mass spectrometry (GED/MS) and by quantum chemical calculations (DFT and MP2). Comparison of these results with those for non-substituted pyridine N-oxide and 4methylpyridine N-oxide CH 3 -PyO, demonstrate strong substitution effects on structural parameters and electron density distribution. The presence of the electron-withdrawing eNO 2 group in para-position of 4-NO 2 -PyO resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…If the laplacian at a point is positive, that means the average of that point's neighbour's values is greater than the value at that point and if it is negative, the neighbour's value is lower than the value of that point. It was also shown that, laplacian electron density for NU/POM(NO 2 ) systems had the lowest value that was the only negative recorded (−0.0650) and with the highest electronic energy density (−0.1284) which indicate the occurrence of shared interaction, thus implies the covalent nature of the chemical bonds for both molecules that has been studied [32–35] . In addition, Yar et al [36] said the laplacian of the electron density with energy density are in the range of H‐bonding.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…If the laplacian at a point is positive, that means the average of that point's neighbour's values is greater than the value at that point and if it is negative, the neighbour's value is lower than the value of that point. It was also shown that, laplacian electron density for NU/POM(NO 2 ) systems had the lowest value that was the only negative recorded (−0.0650) and with the highest electronic energy density (−0.1284) which indicate the occurrence of shared interaction, thus implies the covalent nature of the chemical bonds for both molecules that has been studied [32–35] . In addition, Yar et al [36] said the laplacian of the electron density with energy density are in the range of H‐bonding.…”
Section: Resultsmentioning
confidence: 93%
“…It was also shown that, laplacian electron density for NU/POM(NO 2 ) systems had the lowest value that was the only negative recorded (À 0.0650) and with the highest electronic energy density (À 0.1284) which indicate the occurrence of shared interaction, thus implies the covalent nature of the chemical bonds for both molecules that has been studied. [32][33][34][35] In addition, Yar et al [36] said the laplacian of the electron density with energy density are in the range of H-bonding.…”
Section: Quantum Theory Of Atoms In Molecules Descriptionmentioning
confidence: 99%
“…The shape of the mass spectra of pyridine oxides 1 and 2 corresponds to the shape of the mass spectra recorded during synchronous electronographic/mass spectrometric (EG/MS) studies [ 18 , 19 ], despite the fact that the vapor temperature of the studied compounds in EG/MS experiments exceeded the temperature range of our research by 20‒50°C. This allows us to conclude that pyridine oxides 1 and 2 are thermally stable over a wider temperature range.…”
mentioning
confidence: 71%
“…Our quantum-chemical study of a number of N- oxides [ 17 ] made it possible to detect the effect of donor and acceptor substituents on some characteristics of the N→O bond, whereas the electron diffraction study of 4-CH 3 PyO 1 [ 18 ] and 4-NO 2 PyO 2 [ 19 ] molecules helped to refine their structure (Fig. 1 ).…”
mentioning
confidence: 99%
“…It has been assumed that the presence of the nitro group in the substituted pyridine N-oxides is responsible for a substantial increase in the antifungal activity. 25 In this study, NPNO and p-aminobenzoic acid (PABA) were selected as the model compounds for three reasons. First, NPNO is a yellow platelike crystal and PABA is a white needlelike (α) or platelike (β) crystal, while the cocrystal of the two is bright orange, which makes it easy to determine the formation of the cocrystals during both the grinding and solution crystallization experiments.…”
Section: Introductionmentioning
confidence: 99%